2020
DOI: 10.1177/1060028020934879
|View full text |Cite
|
Sign up to set email alerts
|

Geosocial Factors Associated With Adherence to Statin Medications

Abstract: Background: Individual patient characteristics, social determinants, and geographic access may be associated with patients engaging in appropriate health behaviors. Objective: To assess the relationship between statin adherence, geographic accessibility to pharmacies, and neighborhood sociodemographic characteristics in Michigan. Methods: The proportion of days covered (PDC) was calculated from pharmacy claims of a large insurer of adults who had prescriptions for statins between July 2009 and June 2010. A PDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…to some overseas studies [44][45][46], we did not find an association between socioeconomic status and statin adherence except for patients living in the most deprived areas. This may partly reflect the variation in how socioeconomic status is measured across countries and studies.…”
Section: Plos Onecontrasting
confidence: 96%
“…to some overseas studies [44][45][46], we did not find an association between socioeconomic status and statin adherence except for patients living in the most deprived areas. This may partly reflect the variation in how socioeconomic status is measured across countries and studies.…”
Section: Plos Onecontrasting
confidence: 96%
“…No association was found for distance to most frequently utilised pharmacy in this study. This finding aligns with two other studies, one involving n=6532 T2DM patients enrolled in Medicaid in the Greater Chicago region, which focused on adherence to angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers ( Syed et al, 2016 ), and another which focused on n = 174,146 persons enrolled in commercial insurance products in Michigan taking statin medication ( Erickson et al, 2020 ). Walgreens®, a nationwide U.S. pharmacy chain, claims that 76 percent of the entire U.S. population is within 5 miles of a Walgreens® pharmacy, and 40 percent of Medically Underserved Areas are within a 15-min drive-time of a Walgreens® pharmacy ( Taitel, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…The finding that T2DM patients living in areas with greater social vulnerability were more likely to be non-adherent after adjustment for individual factors is supported by a recent study of patients undergoing statin therapy, where associations were observed between lower levels of adherence and lower neighbourhood socioeconomic status and urban-versus rural-dwelling residents ( Erickson, Bravo, & Tootoo, 2020 ). This is the first time to our knowledge that the CDC/ATSDR Social Vulnerability Index has been used to study potential social determinants of medication adherence.…”
Section: Discussionmentioning
confidence: 85%
“…Statin adherence has been reported to be associated with higher socioeconomic status and higher educational attainment. 17 , 18 A Swedish study found that patients with ≤ 9 years of education were less likely to use statin medications compared to patients with more than 12 years of educational attainment (odds ratio: 0.89 (95% CI: 0.84–0.94). 33 However, the finding is not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, socioeconomic and demographic characteristics of statin users may have changed over the last decades, but this possibility has not been addressed by the existing literature. Furthermore, statin adherence has been associated with higher socioeconomic status, [15][16][17][18] which is associated with longer survival in patients with cirrhosis. 19 Therefore, it remains unclear if some of the beneficial effects attributed to statin use could in fact be caused by favourable socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%